Analisis Penerapan Pembelajaran Fisika Pada Kompetensi Profesional Mahasiswa PLP Tahun 2023 Program Studi Pendidikan Fisika - Hermawan Susanto; Nur Adh Dhuha (LPPM Politeknik Pratama, 2023)
This research uses a descriptive method with a qualitative approach which aims to describe and analyze the pedagogical competence of PLP students in 2023, FKIP Physics Education Study Program, Riau University as future teacher candidates. Professional Competency in Law Number 14 of 2005 concerning Teachers and Lecturers, Professional Competency is the ability to master subject matter broadly and in depth (Law No. 14 of 2005 concerning Teachers and Lecturers, 2009: 33). The sample of research data taken was 40 people from 7th semester Physics Education students who were doing PLP (Introduction to the School Environment). Data is collected and taken by providing questionnaires to find out and measure the learning model used to fulfill the Professional Competencies of a prospective teacher in the future. Data analysis shows indicators of teacher ability in mastery of subject matter; Lesson structure and lesson concepts, Mastery of Competency Standards, Basic competencies and learning objectives, Developing materials creatively and utilizing technology in learning.